Magilock: a reliable control triggering method in multi-channel eye-control systems - Ya-Feng, Niu; Jia-Xin, He; Jin, Liu (Frontiers in Human Neuroscience, 2024)
Eye-tracking technology brings a different human-computer interaction experience to users because of its intuitive, natural, and hands-free operation characteristics. Avoiding the Midas touch problem and improving the accuracy of interaction are among the main goals of the research and development of eye-control systems. This study reviews the methods and limitations of research on avoiding the Midas touch problem. For typical control clicking operations with low fault tolerance, such as mode switching and state selection in an eye-control system, this study proposes Magilock, a more reliable control triggering method with a high success rate in multi-channel eye-control systems. Magilock adds a control pre-locked mechanism between the two interactive steps of eye-control channel positioning control and other interactive channel triggering controls in the multi-channel eye-control system. This effectively avoids incorrect control triggering caused by multi-channel coordination disorder and gaze-point drift. This study also conducted ergonomic experiments to explore the lock and unlock times of the control pre-locked mechanism in Magilock. Taking into account the experimental data and subjective evaluation of the participants, we recommend setting the lock time and the unlock time of Magilock to 200ms.